Continuous element formulations for composite ring-stiffened cylindrical shells - Nam, Le Thi Bich; Cuong, Nguyen Manh; Thinh, Tran Ich; Tran Thanh Dat,; Vu Dinh Trung, (Vietnam Journal of Science and Technology, 2018)
This research studies the free vibration of composite ring-stiffened cylindrical shells by the continuous element method (CEM). The dynamic stiffness matrix (DSM) of the investigated structure has been constructed based on the analytical solutions of the governing equations of motion for composite cylindrical shells and annular plates. By applying the powerful assembly procedure of continuous elements method, natural frequencies and harmonic responses of composite ring-stiffened cylindrical shells have been obtained. In addition, the proposed model allows extracting exactly ring-stiffener vibration modes by choosing appropriate points of response. Numerical examples have confirmed many advantages of the developed model.